Women Leading in Higher Education: An Empirical Study of Challenges, Strategies, and Recommendations - KAMEL, GHADA MAHMOUD MOHAMED (2025)
Women have been breaking barriers and making tremendous strides in leadership in higher education. In recent years, there has been a lot of emphasis on women's leadership in this field, and its impact and implications. This study explores women's leadership challenges in higher education in the UAE and what strategies they employ to address them. Using a mixed-methods approach, the study aggregates qualitative results from five semi-structured interviews with women in leadership roles with quantitative results from a survey of 52 female higher education professionals. The findings reveal that work–life conflict, gender stereotypes, and organisational obstacles present a strong challenge to women's leadership. Counter to these barriers, various successful strategies like mentorship, professional development, networking, and resilience competencies were mentioned by the participants. Notably, the study identifies a key role for emotional intelligence, strategic planning, and organisational policy changes in fostering a leadership culture that is inclusive. The study underlines how effective policies such as family-friendly workplace regulations, mentoring programmes, and clear promotion standards help to create fairer leadership prospects. Higher education institutions, policymakers, and women seeking leadership roles are advised to undertake systemic reforms to promote women in leadership. Lastly, the study encourages women's empowerment in educational leadership, with practical recommendations to institutions in terms of how to develop a more diversified and inclusive leadership.